2019
DOI: 10.1103/physrevb.100.241104
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium orbital transitions via applied electrical current in calcium ruthenates

Abstract: Simultaneous control of structural and physical properties via applied electrical current poses a key, new research topic and technological significance. Studying the spin-orbit-coupled antiferromagnet Ca2RuO4, and its derivative with 3% Mn doping to alleviate the violent first-order transition at 357 K for more robust measurements, we find that a small applied electrical current couples to the lattice by significantly reducing its orthorhombicity and octahedral rotations, concurrently diminishing the 125 K-an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 32 publications
2
32
1
Order By: Relevance
“…However, the behavior of the current-driven transition observed in Ca 2 RuO 4 appears to be inconsistent with these expectations [28][29][30][31][32][33][34][35]. In this material the insulating phase is destroyed at threshold fields (E th ∼ 40 V/cm) that are several orders of magnitude smaller than the fields required for a significant excitation of carriers, while it has been reported that the global temperature of the system remains below the equilibrium critical temperature [29].…”
Section: Introductionmentioning
confidence: 82%
“…However, the behavior of the current-driven transition observed in Ca 2 RuO 4 appears to be inconsistent with these expectations [28][29][30][31][32][33][34][35]. In this material the insulating phase is destroyed at threshold fields (E th ∼ 40 V/cm) that are several orders of magnitude smaller than the fields required for a significant excitation of carriers, while it has been reported that the global temperature of the system remains below the equilibrium critical temperature [29].…”
Section: Introductionmentioning
confidence: 82%
“…In case of the longitudinally polarized Higgs mode, its existence is precluded when no orbital degree of freedom is present, such as is the case for S = 5 2 in an undistorted octahedral weak ligand field. In this case, orthogonality ensures that matrix elements of the form m|J z |0 are zero, and thus by Eq.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The magnetism inherent to Hund's metals 1 and their parent multiorbital Mott states 2 is believed to play a crucial role in many of their anomalous electronic properties, 3 ranging from unconventional superconductivity, 4 to violations of Fermi liquid theory, to the recent unveiling of novel nonequilibrium states. 5 This is perhaps most clearly illustrated in the range of emergent phenomena that appear in 4d transition metal oxides-where an intermediate coupling regime manifests. In this regime, spin-orbit coupling, magnetic exchange, and crystalline electric field energies compete with one another on equal footing in determining a material's ground state properties.…”
Section: Introductionmentioning
confidence: 99%
“…1a), and this study demonstrates that it works particularly well for materials whose low energy physics is dictated by competing interactions [1][2][3][6][7][8][9][10][11][12][13][14][15] leading to multiple nearly degenerate states. Consequently, a resulting alteration in structural distortions (e.g., rotations/tilt of octahedra or Ir-O-Ir, and Ru-O-Ru bond angles) can be associated with disproportionately strong responses in physical properties, facilitating a different ground state to emerge 2,6,[16][17][18][19][20][21][22][23][24] . We would like to emphasize a crucial role of the bond angles that can significantly affect the physical properties via strong SOI and magnetoelastic coupling 2,6,17,18,20,22,24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a resulting alteration in structural distortions (e.g., rotations/tilt of octahedra or Ir-O-Ir, and Ru-O-Ru bond angles) can be associated with disproportionately strong responses in physical properties, facilitating a different ground state to emerge 2,6,[16][17][18][19][20][21][22][23][24] . We would like to emphasize a crucial role of the bond angles that can significantly affect the physical properties via strong SOI and magnetoelastic coupling 2,6,17,18,20,22,24,25 . The field-altering technology allows the Zeeman effect to exert a torque on the spin, which couples to the orbit via SOI; the orbit in turn needs to readjust and tilts the octahedron, thus altering the bond angles.…”
Section: Introductionmentioning
confidence: 99%